(untitled) (The Pakistan Development Review, 1993)
In this paper we address the following question: How great have been the costs to Pakistan, in tenns of income growth foregone over the last three decades, of relatively low investments in education, and especially in the education of girls? We use the results of an econometric analysis of the relationship between education and economic growth in a cross-section of countries to compare Pakistan’s actual rate of growth and recent levels of output with what they might have been had Pakistan achieved education enrollment rates observed in three rapidly growing East Asian economies: Indonesia, Republic of Koreal and Malaysia. Our analysis suggests that foregone income growth has been large. For example, if female enrollment in primary school had been as high as male enrollment in 196 i.e. 46 percent instead of 13 percent, we estimate that Pakistan’s 1985 per capita income would have been more than 15 percent greater than it was. (In 1960, male enrollment rates in primary school in Indonesia, Korea and Malaysia were 58,83 and 89 percent, respectively.) We recognise that education investments have social as well as economic benefits, e.g. the lower infant mortality rates of better-educated mothers, and that gains in income growth alone are a poor measure of overall development.